2015
DOI: 10.5935/0103-507x.20150007
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusions in septic shock: is 7.0g/dL really the appropriate threshold?

Abstract: ObjectiveTo evaluate the immediate effects of red blood cell transfusion on central venous oxygen saturation and lactate levels in septic shock patients with different transfusion triggers.MethodsWe included patients with a diagnosis of septic shock within the last 48 hours and hemoglobin levels below 9.0g/dL Patients were randomized for immediate transfusion with hemoglobin concentrations maintained above 9.0g/dL (Group Hb9) or to withhold transfusion unless hemoglobin felt bellow 7.0g/dL (Group Hb7). Hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The eight included RCTs ranged in publication year from 1999 to 2019 and contained a total of 3415 patients 10 22 23 25–29. The patient population sizes of the included trials were very diverse, ranging from 44 to 998.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The eight included RCTs ranged in publication year from 1999 to 2019 and contained a total of 3415 patients 10 22 23 25–29. The patient population sizes of the included trials were very diverse, ranging from 44 to 998.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this study was the first comprehensive meta-analysis to address different transfusion thresholds among critically ill and perioperative patients, but it lacked a valid analysis of secondary outcomes which were noteworthy factors for the effects of RBC transfusions. Furthermore, Chong and colleagues also conducted an updated analysis on the effects of RBC transfusion, which included two more RCTs other than the same 10 trials included in Fominskiy’s study 18 19 23 30. These results suggested that RBC transfusion with restrictive threshold significantly reduced the risk of overall 30-day mortality (OR: 0.82, 95% CI: 0.70 to 0.97, p=0.019) when compared with that with liberal threshold, accompanied with declining risk of stroke/transient ischaemic attack (OR: 0.63, 95% CI: 0.40 to 0.99, p=0.04), transfusion reactions (OR: 0.48, 95% CI: 0.29 to 0.80, p=0.005), allogenic blood exposure (OR: 0.04, 95% CI: 0.01 to 0.14, p=0.001) and length of hospital stay (95% CI: 0.42 to 1.64, p=0.001), hinting the safety of using restrictive transfusion protocol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations